The Effect of Special Training of the Dynamic Lactic Method in the Development of some Physiological Variables and the Jump Shot Accuracy for Young Basketball Players - et. al., Layth Rasim Abbas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims at preparing dynamic tactical exercises for young basketball players identifying the effect of dynamic lactic exercises in some physiological variables and accuracy of jump shooting for young basketball players. The researchers use the experimental method though experimental design of equivalent groups pre and post measurements as it is appropriate to the nature of the research. The research community is determined by 15 basketball players from the Imam Al-Muttaqin Sport Club for the 2015-2016 season. The researchers use a comprehensive limited method when selecting the research sample. physiological variables were studied (pulse rate, blood lactic acid concentration, maximum oxygen consumption Vo2 Max). Some of the most important findings the researchers came up with was that dynamic lactate exercises had an effect in improving the heart rate before and after the fatigue as well as the level of lactic acid before and after fatigue and Vo2 Max level.